Umbilical Discharge - Moniruddin, ABM; Raihan, Hossain Md Sabbir; Khanom, Mst Nazmun Nahar; Hasan, Tanvirul; Ferdous, Baikaly; Khan, M Rashed; Rouf, M Abdur (KYAMC Journal, 2022)
An umbilical discharge is itself not a disease, but it is a symptom of many diseases. In children, it may be found to be associated with an underlying congenital abnormality like persistent OMD (Omphalo-mesenteric Duct) or Vitelline cysts or sinuses or umbilical granuloma or a diverticulum like the Meckel’s diverticulum which may possess ectopic gastric or pancreatic or even colonic mucosa, or the persistent allantois or a urachal cyst or an infected urachus etc. Umbilical discharge though rare in adults, it may be caused by diverse congenital or acquired conditions. The most common causes of umbilical discharge in adults are such acquired conditions as pilonidal sinus disease, infection of hair tufts and foreign bodies4, and specific and non-specific acute and chronic inflammation and abscess of the umbilicus, infected omphalolith etc. Very rarely the discharge may be due to endometriosis or metastatic carcinoma, umbilical hernia ulceration etc. Discharging umbilical abscess may be caused by bacteria that can enter as a result of penetrating trauma, rupture of the bowel, or abdominal surgery. Irrespective of aetiology, umbilical discharge is a distressing condition for the patient and the family members. Appropriate diagnostic aids and successful management strategies are now available. If not associated with malignant diseases or irreversible complications, the prognosis is excellent. KYAMC Journal Vol. 13, No. 01, April 2022: 50-55